Ways toward a European vocational education and training space : a "bottom-up" approach - Blings, Jessica [Verfasser]; Spöttl, Georg [Verfasser] (My University, 2008)
"This paper seeks to concentrate on bottom up approaches in order to promote a European vocational education and training (VET) concept. The overall aim of this article is to demonstrate that sophisticated approaches still have a chance of becoming common practice in European countries. The centre of the article is the discussion of a core occupational profile called ECO-recycler, which tends to be an alternative to the discussion of a uniform European Qualification Framework. The method of participatory discourse is applied in order to shape a VET space jointly with European partners. However, the partnership should not only discuss an abstract level because the implementation of the ECO-recycler is the main target of the discourse and it will be demonstrated how it works." (Autorenreferat, BIBB-Doku)
Keywords: I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; Europäischer Bildungsraum; Europäischer Kernberuf; Berufsbild; Qualifikationsprofil; Kreislaufwirtschaft; Curriculumentwicklung; Internationale Zusammenarbeit